Chapter Dante presente, Dante assente. Il dibattito sulla cancellazione dai programma scolastici bulgari - Karapetkova, Daria (Biblioteca di Studi di Filologia Moderna, 2022)
One of the initiatives on the occasion of the 700th anniversary of Dante's death, carried out in Bulgaria in October 2021, consisted in the publication of a monographic issue of the weekly Literaturen vestnik in a bilingual version with the title "Ancora attuale, sempre divino: Literaturen vestnik celebra Dante." Among the thematic features contained in this issue, an important place is occupied by three surveys conducted among Bulgarian secondary school teachers, university lecturers and poets. The surveys aim to outline how Dante's work is currently perceived and to comment on the fact that - unbeknownst to most people - the Divina Commedia has been excluded from the literature curricula since the 2018-19 academic year.